Health Education Teaching Materials Through Comic Media for Primary School Students - Sudarmono, Martin; Hanani, Endang Sri (Journal of Health Education, 2020)
Background: Teaching media is one of several instruments used by teachers to help them carry out the teaching and learning. However, based on the results of the preliminary study, only 30% of primary schools use learning media. Methods: This study is developmental research. The development procedures in this study include: (1) conducting a need analysis, (2) making a draft of the initial product, (3) validating experts, (4) improving the draft initial product, (5) first trial, (6) initial product revisions, (7) second trial, (8) revision of final products and (9) final products of the health education teaching materials. Results: This study obtained 85% of health education experts evaluation data and 95% of media experts so that the average percentage was 90% and included in the "very good" category. The results of the first trial reached 86% which is categorized as "good". The results of the second trial on the field received that the average percentage of 93.5% is included in the "very good" category. The results of student responses are as follows: 1) Primary School of 01 Sekaran obtained 86%, 2) and Primary School of 02 Sekaran obtained 92%. Since the students can understand and explain the material respectively. Conclusion: Teaching materials of health education through comic media are very appropriate to be used.